2020
DOI: 10.1039/c9tb01927h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bactericidal activity of brucite through partial copper substitution

Abstract: Copper substituted Mg(OH)2 nanoplatelets exhibit high bactericidal activity towards S. aureus and E. coli with fast kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Table S2 in ESI† displays the results. As we previously showed, 37 Mg(OH) 2 nanoparticles have poorly bactericidal performances in the evaluation conditions we used. Its presence as secondary phase in the Cu 0.85 Mg 0.15 (OH) 2 and Cu 0.80 Mg 0.20 (OH) 2 samples only further increases the slowing down of the bactericidal kinetics of the mixed hydroxides.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Table S2 in ESI† displays the results. As we previously showed, 37 Mg(OH) 2 nanoparticles have poorly bactericidal performances in the evaluation conditions we used. Its presence as secondary phase in the Cu 0.85 Mg 0.15 (OH) 2 and Cu 0.80 Mg 0.20 (OH) 2 samples only further increases the slowing down of the bactericidal kinetics of the mixed hydroxides.…”
Section: Resultsmentioning
confidence: 84%
“…1). In our previous study, 37 TG-MS evolved gas analyses showed that nanoplatelets of Mg(OH) 2 starts decomposing above 300 °C by releasing water molecules (peak at 350 °C in the m / z = 18 spectrum). The step in the tail of the TG curve of the Cu 0.8 Mg 0.2 (OH) 2 sample is therefore ascribed to the thermal decomposition of this secondary phase Mg(OH) 2 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations